Respuesta :

Answer:

C 2

Step-by-step explanation:

This is a parabolic function

Notice how we go negative and then positive

y = ax^2 +bx+c

Let x = 0

-5 = a(0) + b(0) +c

c = -5

y = ax^2 + bx -5

Let x = 3

4 = a(3)^2 +b(3) -5

Let x=-3

4 = a(3)^2 -b(3) -5

Add the two equations

4 = a(3)^2 +b(3) -5

4 = a(3)^2 -b(3) -5

----------------------------

8 = 2a (3)^2 - 10

18 = 2 a(9)

18 = 18a

a =1

Solving for b

4 = 1(3)^2 -b(3) -5

4 = 9 -3b -5

4 = 4 -3b

0 = -3b

0 =b

The equation is

y = (x)^2  -5

Letting y = -1

-1 =x^2 -5

Adding 5 to each side

4 = x^2

Taking the square root of each side

±2 = x

x= ±2

Given the choices

Answer:

The answer is C

Step-by-step explanation:

ACCESS MORE